KEBUTUHAN PERAWAT DALAM MEMBERIKAN ASUHAN KEPERAWATAN PALIATIF PADA ANAK: LITERATURE REVIEW - Adistie, Fanny; Lumbantobing, Valentina; Maryam, Nenden Nur Asriyani; Hendrawati, Sri (STIKes Maharani Malang, 2018)
Providing palliative nursing care to children with terminal illnesses, as well as children in dying conditions is a challenge for the nurses themselves. Nurses must be able to provide optimal pediatric palliative care. The purpose of this literature review is to identify what are the needs of nurses in providing pediatric palliative care. The search strategy is conducted through the Proquest, EBSCO, and Science Direct databases. The keywords used are nurse, needs, palliative care, end of life care, terminal care, children, and pediatric. Inclusion criteria are English-language articles published in 2008-2018. The study was criticized by using the Critical Appraisal Tool from JBI and for mixed method studies using Mixed Methods Appraisal Tool Version 2018. Eight studies met the criteria for review. The results of the review showed that in providing pediatric palliative care nurses need adequate support in dealing with stress and fatigue and require specific education and training related to pain management and end of life communication to improve nurses' abilities and competencies in providing pediatric palliative care.Therefore, it is important for the hospital to facilitate nurses in attending education and training related to pediatric palliative care so that nurses can optimally provide palliative care to children in an effort to improve the quality of life for children and their families.